An applied study of B-type natriuretic peptide in a non-dialysis population with chronic kidney disease - WANG Xiao-yu; XU Mi-qing (Linchuang shenzangbing zazhi)
The 2018 US Kidney Data System report shows that more than 30 million US adults may suffer from chronic kidney disease(CKD),and cardiovascular disease(CVD)is the main cause of death from chronic renal failure.Therefore,early identification of clinical manifestations of CVD and early intervention in CVD are of vital importance.Cardiac biomarkers,such as B-type natriuretic peptide(BNP)and N-terminal pro-B-type natriuretic peptide(NT-proBNP),are commonly used to diagnose congestive heart failure(CHF)in symptomatic patients.There is sufficient evidence that these biomarkers can be used to assess the severity of the disease and its prognosis.However,in CKD patients,because the decrease of renal clearance rate may affect the plasma level of these biomarkers,BNP faces challenges in diagnosis utility and prognosis evaluation.It is difficult to distinguish cardiac-induced heart failure from renal-induced chronic BNP elevation in non-dialysis CKD patients.This review reviews the physiological functions of the natriuretic peptide BNP in detail,and briefly discusses the characteristics of CVD in a non-dialysis CKD population,the changes of BNP,influencing factors and possible mechanisms,and its predictive significance for CVD.